Scientific Writing Workshop Improves Confidence in Critical Writing Skills among Trainees in the Biomedical Sciences - Emily Wortman-Wunder (American Society for Microbiology, 2020)
Written communication is a key research skill, yet the current model of pre- and postdoctoral training in the biomedical sciences lacks consistent formal training in this area, leading to crises of confidence when tackling research writing. A 15-hour non-credit workshop, “Secrets of Successful Scientific Writing,” was developed in collaboration with an experienced instructor of scientific writing. The workshop consisted of six 2.5-hour sessions and was offered six times; a total of 126 trainees attended over these six offerings. Topics included strategies to engage the audience, principles of psychological linguistics to maximize sentence effectiveness, conventions of biomedical journal writing, technical writing and the history of scientific publishing, and two sessions on grant writing. Student confidence in and familiarity with targeted writing skills were assessed by self-evaluation questions administered immediately before and after each session. The workshop was determined to be effective at improving the confidence of participants regarding specific writing skills in the biomedical sciences, with all but two of the measures showing that the workshop had a large effect size. We conclude that a short, structured workshop can help improve the confidence and knowledge of pre- and postdoctoral writers, preparing them to better meet the writing challenges of their professional careers.